Por uma Biblioteca Viva: uma proposta para o ensino da leitura - Sousa, Ana Carolina de (2021)
This dissertation is the result of a research developed in the Graduate Program in Teaching (PPGEN), at the Unversidade Estadual do Norte do Paraná (UENP). With purpose that libraries can be a space for development of the discursive practice of reading, we developed an research-action, aiming to answer the question: How can the methodology of ordering and sequencing of reading questions contribute that the library activity advisor assists the child improving reading comprehension? So, the general objective is to elaborate a theoretical-methodological proposal, aimed at activity advisors, for the reading teaching of children from 10 to 12 years old, attend a library environment. The proposal is based in the methodology of ordering and sequencing of reading questions (SOLÉ, 1998; FUZA; MENEGASSI, 2017; FUZA; MENEGASSI, 2018) and has organizing axis the wonderful tale. In order to answer the guiding question, we elaborated and implemented a diagnostic theoreticalmethodological proposal. The participants were five children, who already had the habit of attending the library, lending books and participating in actions to promote the reader. The results of the analyses on the answers presented by the participants demonstrate that the methodology of ordering and sequencing of reading questions can help the library activity advisor assisting the child in improving reading comprehension. Therefore, in search of an improvement, we elaborated a new proposal, which is then established as our Educational Product, structured in a didactic notebook.